Art as Phenomenon - Kolev, Ivan (B@belonline, 2022)
The Philosophy of Art class offers students an approach that intends to avoid the traditional limitation of students’ attention to the work-author-viewer triad. Instead, students are offered a philosophical reflection on art in which the emphasis falls on explicating the ‘perspectives’ that are involved in the meaning constitution of a whole, which in this approach we call ‘the phenomenal being of art’. Each perspective has a ‘figure’ representing it and its perspective is described phenomenologically, given that the is to explicate the meaningful contribution of this figure and its perspective in constituting the ‘phenomenal being of art’. This approach has similarities with two other art’s conceptions: the historical one of Paul Frankle and the institutional one of Arthur Danto and George Dickie.